KONJUNGSI DALAM LIRIK LAGU-LAGU KELOMPOK BAND AVENGED SEVENFOLD PADA ALBUM NIGHTMARE - GONIBALA, RELIGA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research is entitled â€œConjunction in the Songsâ€™ lyiric of Avenged Sevenfold Group Band in the album â€œNightmareâ€ that is also known as A7x. In the aspect of function, conjunction is divided into coordinative conjunction and subordinative conjunction. The object of this study is to see the conjunctions in the lyirics and see the function and meaning of the conjunctions. The method used is descriptive, and the concepts of Payne (2011), and Quirk and Greenbaum (1999). The result of this research shows that,Â the coordinate conjunctions found are and, but, or, for, so and still. Meanwhile the subordinate conjunctions found are where, when, that, before, how, as long as, as soon as, since, if, because, while, until, than, once, andÂ as. Coordinate conjunctions connect words, phrases, clauses, and sentences. Meanwhile subordinate conjunctions connect clauses as in the concept. Besides, the subordinate conjunctions found also connect phrase and clause, and clause and sentence where these two things are not appropriate with the concept used, and the meaning of the conjunctions are fit to the concept. Keywords : Conjunction, Coordinate and subordinate conjunction, Avenged Sevenfod Â